(untitled) (Journal of Educational Development and Practice, 2023)
Although significant progress has been made to rectify gender imbalances in education and development, socio-cultural and economic challenges still constitute barriers to females’ educational attainment. Using a qualitative research approach involving 16 participants and data collected through semi-structured interviews, we explored socio-cultural and economic factors that constitute barriers to females’ educational attainment in a rural district in Ghana. From the thematic analysis of the interview data, the findings showed that socio-cultural barriers – driven by traditional gender roles, cultural norms, along with economic barriers, including poverty and limited resources – hinder females’ educational attainment. Drawing on social norm and gender performance theories, we argue that socio-cultural and economic barriers are critical issues that shed light on the complex challenges females in rural communities face as they strive for educational attainment. We recommend the implementation of local-level awareness campaigns and community engagement initiatives to transform negative perceptions surrounding females’ education in rural communities.